Experimental Investigation of Preheated Air Effects with Multi-line of Fuel Injection (LPG) on a Tubular Combustor of Micro Gas turbine (Journal of University of Babylon for Engineering Sciences, 2018)
This work presents the experimental investigation carried out for preheated air with multi-line of fuel injection in a tubular combustor of micro gas turbine to produce high performance, Low emission and distributed flameless combustion, flameless combustion characterized by dispersed and homogeneous flame and temperature uniformity under the conditions of preheated air and adequate amount of recirculation of products gases. System performance, emissions gases and temperature measured at variable inlet air mass flow rate and gas fuel LPG flow rate for variable flow of secondary fuel radial inward 90º injection in secondary zone F2 with respect main fuel injector flow rate F1. concluded that maximal preheated air mass flow rate, with distributed fuel injection with high speed of fuel flow in the main and secondary injectors for each cases promotes the formation of distributed dark pal blue flame combustion, for 3.2 g/s of fuel flow rate with 1mm main injector holes diameter and 8 radial inward 90º holes with 1cm depth of injection ports concluded, lower carbon monoxide CO emissions and decreasing in unburned hydro carbon UHC emissions from 60 to 20 ppmv with increasing in power generation from 2.7 to 5.2 kW and decreasing in specific fuel consumption (S.F.C) from 4 to 2.8 kg/kWh.